Frail hypertensive older adults with prediabetes and chronic kidney disease: insights on organ damage and cognitive performance - preliminary results from the CARYATID study - Gaetano Santulli; Valeria Visco; Michele Ciccarelli; Mario Nicola Vittorio Ferrante; Piero De Masi; Antonella Pansini; Nicola Virtuoso; Armando Pirone; Germano Guerra; Veronica Verri; Gaetano Macina; Alessandro Taurino; et al. (Cardiovascular Diabetology, 2024)
Abstract Background Hypertension and chronic kidney disease (CKD) pose significant public health challenges, sharing intertwined pathophysiological mechanisms. Prediabetes is recognized as a precursor to diabetes and is often accompanied by cardiovascular comorbidities such as hypertension, elevating the risk of pre-frailty and frailty. Albuminuria is a hallmark of organ damage in hypertension amplifying the risk of pre-frailty, frailty, and cognitive decline in older adults. We explored the association between albuminuria and cognitive impairment in frail older adults with prediabetes and CKD, assessing cognitive levels based on estimated glomerular filtration rate (eGFR). Methods We conducted a study involving consecutive frail older patients with hypertension recruited from March 2021 to March 2023 at the ASL (local health unit of the Italian Ministry of Health) of Avellino, Italy, followed up after three months. Inclusion criteria comprised age over 65 years, prior diagnosis of hypertension without secondary causes, prediabetes, frailty status, Montreal Cognitive Assessment (MoCA) score < 26, and CKD with eGFR > 15 ml/min. Results 237 patients completed the study. We examined the association between albuminuria and MoCA Score, revealing a significant inverse correlation (r: 0.8846; p < 0.0001). Subsequently, we compared MoCA Score based on eGFR, observing a significant difference (p < 0.0001). These findings were further supported by a multivariable regression analysis, with albuminuria as the dependent variable. Conclusions Our study represents the pioneering effort to establish a significant correlation between albuminuria and eGFR with cognitive function in frail hypertensive older adults afflicted with prediabetes and CKD.